2014
DOI: 10.1111/1475-6773.12232
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Federal Health Reform in the States: Who Is Included and Excluded and What Are Their Characteristics?

Abstract: Over 15 percent of income-eligible uninsured nonelderly adults will be potentially excluded from the ACA coverage expansions due to their immigration status. Policy makers must be careful to exclude ineligible nonelderly adults before estimating the impact of the ACA on coverage rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…The ACA fundamentally restructured the availability of health insurance in the United States. Since its enactment, adults—who are U.S. citizens or authorized residents—may gain health insurance through two newly established pathways (Fried et al 2014). The first is through the Medicaid expansion, which increased Medicaid eligibility to include not just parents but all adults with annual household income levels up to 138 percent of the federal poverty line (FPL) (Wachino, Artiga, and Rudowitz 2014).…”
Section: Decoupling Health Insurance From Historical Linkagesmentioning
confidence: 99%
“…The ACA fundamentally restructured the availability of health insurance in the United States. Since its enactment, adults—who are U.S. citizens or authorized residents—may gain health insurance through two newly established pathways (Fried et al 2014). The first is through the Medicaid expansion, which increased Medicaid eligibility to include not just parents but all adults with annual household income levels up to 138 percent of the federal poverty line (FPL) (Wachino, Artiga, and Rudowitz 2014).…”
Section: Decoupling Health Insurance From Historical Linkagesmentioning
confidence: 99%
“…Nativity is another variable that affects health insurance coverage greatly because immigrants are less likely to be insured than the U.S.-born [19]. Fried et al found that immigration status had great impact on health insurance under the ACA, since immigrants potentially account for over 15% of uninsured non-elderly adults [20]. Research has shown that the foreign-born, especially recent immigrants, are on average healthier than the U.S.-born [21].…”
Section: Impact Of Nativitymentioning
confidence: 99%
“…Respondents who are currently married are more likely to have health insurance than those who are not currently married because of possible combined incomes and the need to provide health care coverage for the family [31]. The foreign-born are less likely to have health insurance than the U.S.-born partly because of a lack of resources and partly because of norms of health insurance in the home countries [20,22,23]. Non-U.S. citizens are less likely to have health insurance than U.S. citizens due to their lower degree of assimilation to U.S. culture and society [20].…”
Section: Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Medicaid expansion, however, does not apply to all individuals. An estimated 3.5 million non-elderly adults will be excluded from ACA Medicaid expansions and an additional 2 million from health insurance exchanges because of immigration status, as legal permanent residents living in the US for fewer than 5 years and unauthorized immigrants are not eligible for full Medicaid coverage (Fried et al 2014). …”
Section: Introductionmentioning
confidence: 99%